Pro-life, pro-choice and (lack of) proportionality: the legal battle of the swedish midwifes$h - Corsalini, Matteo (Il diritto ecclesiastico, 2022)
The Grimmark and Steen judicial sagas exemplify the tensions between sincerely-religious midwives refusing to terminate pregnancies vis-à-vis the positive obligation of Swedish authorities to provide nationwide abortion services. As will be seen, at the root of these tensions lied a missed opportunity to make a proportionality assessment between abortion and conscience rights both at domestic and ecthr level. This paper first explores the background of the cases at hand, to then speculate about which alternative judicial routes the domestic courts could have taken to give both countervailing interests their due, hence allowing them to co-exist. This essays then offers a critical analysis of the legal battle that the two Swedish midwives fought before the ecthr.